2013
DOI: 10.1182/blood-2013-06-507426
|View full text |Cite
|
Sign up to set email alerts
|

Eradicating acute myeloid leukemia in a MllPTD/wt:Flt3ITD/wt murine model: a path to novel therapeutic approaches for human disease

Abstract: • The Mll PTD/wt :Flt3 ITD/wt mouse is a relevant AML model in which the miR-29b-mediated epigenetics-kinome crosstalk is targetable by bortezomib.• An original liposomal formulation of bortezomib eradicates AML and yields curative therapy for MllThe coexpression of the MLL partial tandem duplication (PTD) and the FLT3 internal tandem duplication (ITD) mutations associate with a poor outcome in cytogenetically normal acute myeloid leukemia (AML). In mice, a double knock-in (dKI) of Mll PTD/wt and Flt3 ITD/wt m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
(45 reference statements)
0
28
0
Order By: Relevance
“…AML blasts transfected with miR-29b also showed significant decreases in SPARC levels at 24 hours ( Figure 8C). We have previously shown that miR-29b is downregulated in AML via a SP1/NF-κB/HDAC inhibitory complex and that pharmacologic disruption of this complex results in miR-29b upregulation and downregulation of direct (i.e., SP1, DNMT3A, DNMT3B) and indirect (i.e., DNMT1, FLT3, KIT) miR-29b targets (45,48,49). Consistent with these reports, we showed that bortezomib at concentrations achievable in vivo (45,50) significantly increased miR29b expression ( Figure 8D) and in turn decreased SP1 and SPARC mRNA and protein levels in Kasumi-1 cells (Figure 8, E and F) and in blasts from 3 different patients with primary AML (numbers 6, 10, and 7) (Figure 8, G and H).…”
Section: Sparc Overexpression Ismentioning
confidence: 99%
“…AML blasts transfected with miR-29b also showed significant decreases in SPARC levels at 24 hours ( Figure 8C). We have previously shown that miR-29b is downregulated in AML via a SP1/NF-κB/HDAC inhibitory complex and that pharmacologic disruption of this complex results in miR-29b upregulation and downregulation of direct (i.e., SP1, DNMT3A, DNMT3B) and indirect (i.e., DNMT1, FLT3, KIT) miR-29b targets (45,48,49). Consistent with these reports, we showed that bortezomib at concentrations achievable in vivo (45,50) significantly increased miR29b expression ( Figure 8D) and in turn decreased SP1 and SPARC mRNA and protein levels in Kasumi-1 cells (Figure 8, E and F) and in blasts from 3 different patients with primary AML (numbers 6, 10, and 7) (Figure 8, G and H).…”
Section: Sparc Overexpression Ismentioning
confidence: 99%
“…) mutations (termed PTD/ITD mice) develop de novo AML with 100% penetrance (28). These PTD/ITD mice were crossed with Rag2 -/-Il2rg -/-mice to produce PTD/ITD/Rag GC KO mice; all died from leukemia as validat- what impact the leukemic environment might have on NK cell homeostasis.…”
Section: Itd/wtmentioning
confidence: 99%
“…Data from murine models and human AML cases suggest that a single mutation is not sufficient to cause AML [12]. For instance, the RUNX-RUNX1T1 and CBFB-MYH11 chimeric oncogenes, resulting from t(8;21) and inv(16)t(16;16) respectively, block myeloid differentiation in murine models but they do not cause an overt leukemic phenotype.…”
Section: Mechanism Of Leukemogenesismentioning
confidence: 99%
“…A multivariable analysis that did not include other molecular genetic markers revealed MLL-PTD status as the only prognostically significant factor for CR duration [85]. Several studies revealed that MLL has been associated with a poor prognosis alone and when associated with FLT3-ITD [12].…”
Section: Mll Prognostic Relevancementioning
confidence: 99%
See 1 more Smart Citation